Sikap Politik Mahasiswa Rantau dalam Pilkada 2024: Studi Kasus ORDA Bangka dan Cianjur di UIN Bandung - Hilmi Taufiqurahman (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2025)
The political attitudes of migrant students during the 2024 Simultaneous Regional Elections reflect a complex interplay of regional identity, political information access, and organizational dynamics within campus-based social structures. This study examines two Regional Student Organizations (ORDA) Bangka and Cianjur at UIN Sunan Gunung Djati Bandung to explore how migrant students’ political preferences are shaped by their dual identity affiliations: their home region and host city. A descriptive qualitative method was employed, involving in-depth interviews, participant observation, and document analysis to uncover the students’ perceptions, orientations, and political behaviors. Findings reveal distinct patterns between the two groups. ORDA Cianjur members tend to develop more homogeneous political opinions through structured discussions focused on local issues, whereas ORDA Bangka members show more diverse and individualistic political attitudes, shaped by informal interactions and strategic regional concerns. Political participation is hindered by structural and psychological barriers, including administrative limitations, geographic distance, and academic obligations. Nevertheless, students in both groups exhibit strong concern for their home regions’ political developments, with candidate selection based more on track record and policy substance than party affiliation. Regional identity, mediated through ORDA, plays a crucial role in fostering political awareness, though its influence varies in strength. These findings suggest that regional student organizations on campus not only serve cultural purposes but also act as platforms for the reproduction of political consciousness among youth. The study underscores the significance of community-based engagement in enhancing political participation among migrant students and calls for institutional support from electoral bodies to reduce participatory constraints in a more inclusive and representative manner